Removal of Dyes of Textile Rejects by Activated Carbon - Elmerzouki, K.; Bimaghra, I.; Khalidi, A. (Journal of Applied Solution Chemistry and Modeling, 2016)
The composition of wastewater from the textile industry varies enormously from one moment to another depending on the nature of the dyes used, the type of tissue, methods used and the concentration of added chemicals. In most cases the dye effluents are characterized by strong color, high temperatures, high and random values of pH, amounts of suspended solids and COD-concentrations close to the limit values set by the draft Moroccan standards. The study of turbidity indicates a variation between 120 and 190 NTU for the three samples. As for their conductivity varies between 5,2 and 20 mS.cm-1. Moreover their pH varies in the field of basic pH. Measuring the temperature of these three samples showed values varying between 25 and 30 Â° C. The levels of suspended solids range between 146,8 and 514,7 mg L-1. The results show that the measured absorbance at 436 nm decreased to 2,020 A and it stabilizes at this value. To the absorbance of the color measured at 525 nm decreases to 3,072 A and it stabilizes. The absorbance measured at the wavelength 620 nm decreases and reaches a minimum value of 1, 918 A after ten hours.